Synthesis of bicyclo[3.1.0]hexanes by (3 + 2) annulation of cyclopropenes with aminocyclopropanes - Muriel, Bastian (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
We report the convergent synthesis of bicyclo[3.1.0]hexanes possessing an all-carbon quaternary center via a (3 + 2) annulation of cyclopropenes with cyclopropylanilines. Using an organic or an iridium photoredox catalyst and blue LED irradiation, good yields were obtained for a broad range of cyclopropene and cyclopropylaniline derivatives. The reaction was highly diastereoselective when using difluorocyclopropenes together with a removable substituent on the cyclopropylaniline, giving access to important building blocks for medicinal chemistry. With efficient methods existing for the synthesis of both reaction partners, our method grants a fast access to highly valuable bicyclic scaffolds with three contiguous stereocenters.